Gambaran Branding Esgrim House Semarang Melalui Media Sosial - Octaviana, Octaviana (Jurnal The Messenger, 2016)
This paper seeks to understand the extent to which social media provides the effect of doing branding Esgrim House Semarang. theoretical basis in this paper is the Narrative Paradigm of Walter Fisher stressed that man is a storyteller and that consideration will be of value, emotion and aesthetics into the basic beliefs of our behavior, or simply refers to the understanding as well as the reaction of everyone when receiving messages the disampaiakan. From these results, it was found that a storyteller admin is his, whereas kususnya twitter and social media instagram serve as tools in the communication process Esgrim House Semarang. So performance this case, social media has a role to introduce products, information centers, as well as archiving online gallery measuring instrument success in branding Esgrim House Semarang.